(untitled) (Al-Academy, 2024)
Every work of art must be composed of matter, which does not take on its characteristics until the artist deals with it. Therefore, the beauty of work of art is not limited the field of the subject matter that it represents, but rather is manifested in the core of the sensory appearance of the work of art and the self that overflows into it from what you possess intellectually give it aesthetics. Therefore, the researcher began study the aesthetic relationship between both the material and the thought process. The research consisted of four chapters: first (the general framework of the research): dealing with the presentation of the research problem, then the basics of the research framework of importance, purpose, and limits. chapter concluded by defining the terms. The second (theoretical framework and previous studies): which included three sections: The first: was devoted studying the concept of aesthetics in two fields: philosophy and artistic work. second section: It specialized in studying the intellectual and performance experience in art, while third section dealt with the intellectual and performance experience in contemporary Iraqi painting. After that, the indicators resulting from the theoretical framework were mentioned. third chapter (research procedures): consists of a research methodology, the research community, as well as selecting the research tool (observation) to achieve its goals. After that, the sample samples were analyzed according a philosophical vision with aesthetic dimensions. While fourth chapter included (results, conclusions, recommendations and proposals)